Ursolic Acid Induces Beneficial Changes in Skeletal Muscle mRNA Expression and Increases Exercise Participation and Performance in Dogs with Age-Related Muscle Atrophy - Scott M. Ebert; Celine S. Nicolas; Paul Schreiber; Jaime G. Lopez; Alan T. Taylor; Andrew R. Judge; Sarah M. Judge; Blake B. Rasmussen; John J. Talley; Christophe A. Rème; Christopher M. Adams (Animals, 2024)
Muscle atrophy and weakness are prevalent and debilitating conditions in dogs that cannot be reliably prevented or treated by current approaches. In non-canine species, the natural dietary compound ursolic acid inhibits molecular mechanisms of muscle atrophy, leading to improvements in muscle health. To begin to translate ursolic acid to canine health, we developed a novel ursolic acid dietary supplement for dogs and confirmed its safety and tolerability in dogs. We then conducted a randomized, placebo-controlled, proof-of-concept efficacy study in older beagles with age-related muscle atrophy, also known as sarcopenia. Animals received placebo or ursolic acid dietary supplements once a day for 60 days. To assess the study’s primary outcome, we biopsied the quadriceps muscle and quantified atrophy-associated mRNA expression. Additionally, to determine whether the molecular effects of ursolic acid might have functional correlates consistent with improvements in muscle health, we assessed secondary outcomes of exercise participation and T-maze performance. Importantly, in canine skeletal muscle, ursolic acid inhibited numerous mRNA expression changes that are known to promote muscle atrophy and weakness. Furthermore, ursolic acid significantly improved exercise participation and T-maze performance. These findings identify ursolic acid as a natural dietary compound that inhibits molecular mechanisms of muscle atrophy and improves functional performance in dogs.